KEBIJAKAN SEKOLAH DAN PARTISIPASI SISWA DALAM PELAKSANAAN PROGRAM SEKOLAH ADIWIYATA DI SMP NEGERI 1 JAKENAN KABUPATEN PATI - Windrianingsih, Sinta Selvi (Universitas Negeri Semarang, 2014)
This study was aimed to determine : 1 ) The policies which were applied in schoolassociated with Adiwiyata School Program in SMP Negeri 1 Pati Jakenan, 2 )student participation in the implementation of Adiwiyata School Program. Thepopulation in this study was all teachers and students in SMP N 1 Jakenan.Sampling was done by proportional random sampling technique which wasobtained 100 people. The data collection technique used the interview,observation, documentation and questionnaires with a simple description analysismethod and percentage description method. The result indicated that the schoolpolicies implemented in SMP Negeri 1 Jakenan which were appropriate whichprovisions of Adiwiyata School and students partisipation in implementing theAdiwiyata School programs were said to be high participation with persentage96,80% and average score of respondents 55,29 (score range 20-60). Theconclusion was that the school policies implemented in SMP Negeri 1 Jakenanwas having environmental concept in accordance with provisions of AdiwiyataSchool. As well as most of the students at SMP Negeri 1 Jakenan highlyparticipated in the implementation of the Adiwiyata School program.